Methodical Aspects of Adequate Basket Formation of Ukrainian Stock Indices (Economics and region, 2019)
There are considered the methodological aspects of forming, reviewing and adjusting the components of the index basket of Ukrainian stock indices in the article, in particular as to the adequacy of reflecting the real state of the market environment in ticker, free-float and weight components. The modern role of the stock index in the economic environment in terms of functional qualities is analyzed. The dependence of stock indices on the limitation of analytical and applied usage, historical retrospective of formation, stochastic features of the index basket are investigated. The article suggests with the improvement of index basket formation by implementation of methodology of adaptive investment systems.
Keywords: stock index; index basket; stock exchange; securities; economic situation